2011
DOI: 10.1002/elps.201100144
|View full text |Cite
|
Sign up to set email alerts
|

A novel hybrid mode of sample injection to enhance CZE sensitivity for simultaneous determination of a pyridine‐triphenylborane anti‐fouling agent and its degradation products

Abstract: We developed a novel hybrid sample injection mode (HSIM) that presents the combination of electrokinetic injection and vacuum injection to enhance detection sensitivity in CZE. Samples were introduced using both vacuum and electrokinetic injections simultaneously, with a water plug injected into the capillary prior to sample introduction (i.e. similarly to field-amplified sample injection, FASI). Using a sample mixture containing an anti-fouling agent applied to ship hulls, pyridine-triphenylborane and its deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…The RSDs of the peak area for PTPB, DPB, MPB, and phenol were obtained as 6.2 -14%, for peak heights of 5.9 -10%, and for migration times of 0.49 -0.62%. The LODs obtained using the FASI-CZE were similar to those obtained using the HSIM-CZE; 35 the LODs of PTPB and DPB were ca. 30 times lower than those for the vacuum injection procedure, but the LODs of MPB and phenol were similar to those for the vacuum injection procedure.…”
Section: Calibration Graphssupporting
confidence: 63%
See 3 more Smart Citations
“…The RSDs of the peak area for PTPB, DPB, MPB, and phenol were obtained as 6.2 -14%, for peak heights of 5.9 -10%, and for migration times of 0.49 -0.62%. The LODs obtained using the FASI-CZE were similar to those obtained using the HSIM-CZE; 35 the LODs of PTPB and DPB were ca. 30 times lower than those for the vacuum injection procedure, but the LODs of MPB and phenol were similar to those for the vacuum injection procedure.…”
Section: Calibration Graphssupporting
confidence: 63%
“…The same BGE, adjusted to pH 9.8, as used in our previous study, 35 was adopted here so that the all analytes would exist as anions in the alkaline BGE. The sample inlet side must be set as the cathode to inject the analytes into the capillary using FASI.…”
Section: Strategy For Separation and Sensitivity Enhancementmentioning
confidence: 99%
See 2 more Smart Citations
“…[6] It was impossible for us to quantify TPBP, DPB, and MPB simultaneously using the HPLC system proposed by the ISO. [11] A hydrolysis and photolysis study of TPBP in water has been reported, [7] and an ecotoxicity study examining microalgae and crustaceans indicates the high toxicity of TPBP and much lower toxicity of the other phenylborane derivatives and some known degradation products. [11] A hydrolysis and photolysis study of TPBP in water has been reported, [7] and an ecotoxicity study examining microalgae and crustaceans indicates the high toxicity of TPBP and much lower toxicity of the other phenylborane derivatives and some known degradation products.…”
Section: Introductionmentioning
confidence: 99%